“efecto de extracto de semilla del árbol de paraíso (melia azedarach) en el control de arrebiatado (dysdercus ruficollis) en algodonero en Juanjí-San Martín” - Marina Trigoso, Edwin Neil (2014)
The research entitled "EFFECT OF SEED EXTRACT PARADISE TREE (Melia azedarach) IN CONTROL ARREBIATADO (Dysdercus ruficollis) ON COTION IN JUANJUI - SAN MARTIN" was to obejtivos determine the effect of seed extract tree paradise on arrabiatado (Dysdercus spp) in cotton growing variety Upland field level American and evaluate application rates in the field, the seed extract of the tree of paradise on arrabiatado in growing American Upland cotton variety. Design Randomized Complete Block (RCBD) with 5 treatments and 4 replications. The treatments were: 4, 6, 8 and 10 liters of extracto.ha-1 anda witness. The conclusions were: Applying seed extract tree paradise with 1 O liters of extracto.ha-1 acted as a repellent but notas an insecticida, the population of nymphs and adults of Dysdercus spp. They decreased with application concentration of the extract from the seed of the tree of Paradise, The percentage of open acoms, closed and falls were directly relatad to the level of infestation by the Dysdercus spp and the best yields were obtained with increasing concentration abstract tree of paradise seed applications, this action because repellency extract protected the acoms cotton. Keywords: seed extract, applications, chinaberry